A Simple Model for the Fields of a Chirped Laser Pulse With Application to Electron Laser Acceleration - Salamin, Yousef I.; Carbajo, Sergio (Frontiers in Physics, 2019)
A simple model is introduced for the fields of a chirped laser pulse. Dynamics of laser-acceleration of a single electron by the fields of a pulse, with a ^4 envelope, is investigated. Multi-GeV energy gains from interaction with pulses of peak intensity I_010^20 W/cm^2, are reported.